THE EFFECT OF LEG MUSCLE STRENGTH, BALANCE AND INTELLIGENCE, TOWARDS THE LEARNING OUTCOMES OF PENCAK SILAT EMPTY-HANDED SINGLE ARTISTIC - Feryan, Feryan Zaifi (Jurnal Inovasi Olahraga, 2023)
This study aims to determine the effects of leg muscle strength, as well as the balance, intelligence, towards the learning outcomes of pencak silat empty-handed single artistic on the students SMAN 2 Tualang. The research method is survey, and the analysis technique is path analysis. This research was held in SMAN 2 Tualang with 122 people of population. The sampling technique used was random sampling, with the total sample of 60 people. The instruments used were a rubric 4 scale (very good, good, enough and less) of learning outcomes of pencak silat empty-handed single artistic, intelligence test with IST (Intelligence Structure Test), leg muscle strength with instrument squat test, and test of balance by using modified bass test of dynamic balance. Based the result of data processing and analysis, the conclusions are: (1) intelligence directly affects the learning outcomes of pencak silat empty-handed single artistic, (2) leg muscle strength directly affects the learning outcomes of pencak silat empty-handed single artistic, (3) balance directly affect the the learning outcomes of pencak silat empty-handed single artistic, (4) intelligence directly affects the balance, and (5) leg muscle strength directly effects the balance.